Surgical treatment for mono-segmental lumbar tuberculosis by single-stage posterior debridement, compact bone grafting and posterior single-segment ﬁxation. Issue 7 (July 2015) - Xu, Zhengquan; Wang, Xiyang; Wu, Ping; Pang, Xiaoyang; Luo, Chengke; Zhang, Penghui; Zeng, Hao; Peng, Wei
Abstract Purpose To evaluate the efficacy and safety of single-stage posterior debridement, compact bone grafting and posterior single-segment fixation for the treatment of mono-segmental lumbar tuberculosis. Methods We enrolled 32 patients with mono-segmental lumbar tuberculosis from January 2005 to April 2011. The severity of damage to the vertebral bodies is not more than 2/3 height. All the patients were treated by single-stage posterior debridement, compact bone grafting and posterior single-segment fixation. Results Patients were followed 21–63 months (43.5 ± 9.5 months). The average Cobb angle decreased to 5.3 ± 3.0° postoperatively from 22.1 ± 6.1° preoperatively. Meanwhile, average 1.8 ± 1.0° loss was observed at last visit. Fusion occurred at 3–9 months (mean 5.1 months). All patients with preoperative neurologic deficit recovered in different degree. 1 with grade B recovered to grade D; 2 with grade C recovered to grade E; 18 with grade D recovered to grade E. No mortality occurred. One patient experienced anti-tuberculosis drug-induced liver dysfunction which was managed successfully with modified anti-TB treatment and hepato-protective treatment. The Oswestry Disability Index decreased from 40.1 ± 4.0 preoperatively to 13.7 ± 3.1 postoperatively. Conclusions Single-stage posterior debridement, compact bone grafting and posterior single-segment fixation is an effective method for the treatment of mono-segmental lumbar tuberculosis.